REDUCING THE CONTENT OF VOCS OF SOFTWOOD KRAFT LIGNINS FOR MATERIAL APPLICATIONS - Anna Katariina Kalliola,; Anne Savolainen,; Taina Ohra-aho,; Greta Faccio,; Tarja Tamminen (BioResources, 2012)
Three laccases, functioning in mild acidic, and one in slightly alkaline conditions, were evaluated in order to reduce low-molecular phenolic VOCs of kraft lignins, which could be used in lignin/natural fibers composites. The potential of a sulfhydryl oxidase to catalyze the oxidation of sulfur containing VOCs (thiols) was also tested in combination with the laccase-catalyzed oxidation. In addition, oxidation at alkaline pH at room temperature that may induce polymerization of phenolics in an analogous manner to the laccase-catalyzed reaction was investigated. Enzyme reactivity towards lignin was evaluated as consumption of oxygen in the reaction solution. The effect of treatments on VOC reduction was determined both by sensing (odorimetry) and chemical (TD-GC/MS, SEC) analyses. Laccases, Lcc2, and MaL from Thielavia arenaria and Melanocarpus albomyces, respectively, showed potential in reducing odors. The most promising results were obtained by oxidizing lignin with O2 at alkaline pH. However, the odor threshold values of the main VOC compounds are extremely low, which poses a challenge to VOC reduction.